Implementation of Phase F Learning in Kurikulum Merdeka: How Well Students Able to Analyze Text? - Kustini, Titin; Ilyas, Rahma (Jurnal Educatio FKIP UNMA, 2025)
"Kurikulum Merdeka" allows teachers to choose the material they find necessary to teach in class. Phase F is a learning phase for grades 11 and 12 at vocational/senior high schools, with the final learning outcome that students should have standard competence in spoken, written, and visual English to communicate according to the situation, purpose, and audience/reader. In this phase, various texts can be used as the main learning material, as they can help students improve their vocabulary, grammar, interpretation, and ability to analyze and produce texts. However, many students face challenges with their basic English skills. A study was conducted to assess students' abilities in analyzing text, specifically analytical exposition texts. Fourteen students majoring in software engineering were involved in the qualitative descriptive study, and data was collected through observation and assessment. Students were required to analyze the text and record it as videos, aiming to increase their technological literacy through mastery of various applications such as Bandicam.The research findings revealed that students showed very good ability in analyzing the generic structure of the text, but struggled with analyzing language features like simple present tense, conjunctions, and terms related to the context. On the positive side, students demonstrated strong technological literacy as they were able to master various video-making applications.